CDs-SA-TAMn nano-composite as well as preparation method and application thereof

By developing CDs-SA@TAMn nanocomplexes, combined with chemical dynamics and photothermal therapy, the problems of side effects and unsatisfactory effects of existing breast cancer treatment methods have been solved, and efficient and accurate tumor treatment effects have been achieved.

CN119868569APending Publication Date: 2025-04-25SHANXI MEDICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411905861.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing breast cancer treatment methods have side effects and local recurrence risks. The single photothermal method is not effective in treating cancer, and other new therapies are needed to improve the tumor suppression rate.

Method used

A CDs-SA@TAMn nanocomplex was developed to modify carbon dots (CDs) by sialic acid and load on a TAMn carrier to form nanocomplexes with tumor microenvironment response capabilities for chemodynamic/photothermal combined therapy.

Benefits of technology

It improves the combined treatment effect of breast cancer, significantly improves the tumor suppression rate, has good biocompatibility and photothermal performance, can achieve controlled release in the tumor microenvironment, and improves the time and space accuracy of treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119868569A_ABST
    Figure CN119868569A_ABST
Patent Text Reader

Abstract

The invention discloses a CDs-SA-TAMn nano-composite and a preparation method and application thereof.A carboxyl group on sialic acid (SA) and an amino group on the surface of the CDs are subjected to an amidation reaction to modify SA on the surface of the CDs, TAMn serves as a carrier to load the CDs-SA, and the novel nano-composite (CDs-SA-TAMn) is constructed. The fluorescence and photo-thermal imaging capability of the nanocomposite is evaluated through in-vitro experiments and cell experiments, and the chemodynamic therapy effect and photo-thermal performance are proved. A Balb / c female mouse is used as a tumor-bearing animal model, blood routine examination, biochemical indexes and HE staining show that the CDs-SA-TAMn nano-composite shows excellent compatibility in a living body, and the tumor combined treatment effect is verified according to indexes such as tumor size and relative tumor volume. The CDs-SA-TAMn nano-composite can be used for preparing medicines for treating and preventing breast cancer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a nanocomposite, and in particular to a CDs-SA@TAMn nanocomposite and a preparation method and application thereof. Background Art

[0002] Breast cancer, as one of the most common types of cancer, has become the leading cause of cancer-related death in women. Although traditional breast cancer treatments (surgery, chemotherapy, and radiotherapy) are effective to some extent, they are often accompanied by significant side effects, including damage to normal cells and tissues, and the risk of local recurrence. In recent years, new tumor treatment methods have emerged, showing significantly improved therapeutic effects. For example, photothermal therapy (PTT) is a treatment method that uses near-infrared light (NIR) to irradiate photothermal agents to non-invasively ablate tumor tissue. It has the advantages of high temporal and spatial precision, low toxicity to normal tissues, and easy implementation. It is an emerging tumor treatment method; chemodynamic therapy (CDT) based on Fenton / Fenton-like reactions is a non-invasive cancer treatment method that achieves selective tumor treatment by using transition metal ions as catalysts in the acidic tumor microenvironment (TME) to convert local hydrogen peroxide (H2O2) into highly toxic hydroxyl radicals (·OH).

[0003] Carbon dots (CDs), as a carbon nanomaterial with excellent photostability, photoluminescence, low toxicity and good water dispersibility, have long been used in disease diagnosis and treatment, biosensing and bioimaging. Jiao et al. prepared highly efficient orange fluorescent carbon dots by hydrothermal method using p-phenylenediamine as precursor for real-time nucleolar imaging in disease diagnosis and biomedical fields. Khan et al. prepared a yellow-orange emitting carbon dot that can spontaneously localize to the nucleolus. The CDs showed excellent fluorescence intensity and photostability and could specifically bind to RNA. CDs with high photothermal properties are ideal candidates for tumor photothermal therapy. Liu et al. synthesized near-infrared emitting CDs with a photothermal conversion efficiency of 59% using urea and citric acid, showing good tumor photothermal performance. Jiang et al. synthesized indocyanine green-derived carbon dots (ICGCDs) with excellent photothermal cycling ability, which can be used for NIR bioimaging and photothermal therapy.

[0004] At present, CDs show a certain tumor inhibition effect in photothermal therapy, but the effect of single photothermal therapy for cancer is often not ideal. The combined use of photothermal therapy and other new therapies can effectively increase the tumor inhibition rate and improve the effect of cancer treatment. Among many new therapies, chemodynamic therapy overexpresses H2O2 in a weakly acidic environment, has high specificity in killing tumors and avoiding damage to normal tissues, and shows obvious advantages in cancer treatment. Summary of the invention

[0005] The purpose of the present invention is to provide a CDs-SA@TAMn nanocomposite and a preparation method and application thereof, so as to obtain at least one active pharmaceutical ingredient in the combined chemodynamic / photothermal therapy of tumors and improve the effect of combined tumor therapy.

[0006] To achieve the above object, according to one aspect of the present invention, there is provided a CDs-SA@TAMn nanocomposite comprising: CDs-SA is a method of modifying the surface of CDs with sialic acid (SA) by reacting the carboxyl group on the SA with the amino group on the surface of CDs to form an amide reaction. TAMn, as a carrier, was used to load CDs-SA.

[0007] According to another aspect of the present invention, provided is a method for preparing the above-mentioned CDs-SA@TAMn nanocomposite, comprising the following steps: Step 1, preparing CDs-SA; Sialic acid (SA) is dispersed in a phosphate buffer solution to obtain a SA solution, NHS and EDC are added to the SA solution and stirred at room temperature to obtain an activated SA solution; CDs are dissolved and added to the activated SA solution, stirred sufficiently at room temperature, and dialyzed to obtain CDs-SA; Step 2, preparation of CDs-SA@TAMn nanocomposites; The TAMn nanosheets were dissolved in deionized water, and then the CDs-SA obtained in step 1 was added, and the CDs-SA@TAMn nanocomposite was obtained after stirring, centrifugation, washing, and freeze-drying.

[0008] Furthermore, in step 1, 20 mg of sialic acid (SA) was dispersed in 10 mL of a phosphate buffer solution at pH 7.4, 24 mg of NHS and 24 mg of EDC were added to the SA solution and stirred at room temperature for 15 min to obtain activated SA.

[0009] Furthermore, in step 1, 20 mg of CDs solid was weighed and dissolved in 10 mL of deionized water. After the CDs were completely dissolved, the activated SA solution was added, stirred at room temperature for 12 h, and then the obtained solution was dialyzed to obtain CDs-SA.

[0010] Furthermore, in step 1, the CDs are synthesized by a hydrothermal method, 1,2,4-triaminobenzene dihydrochloride and spermine are dissolved in deionized water, and the obtained solution is reacted at 90°C for 12 hours and naturally cooled to room temperature; the cooled solution is centrifuged at 15,000 rpm for 10 minutes, the supernatant is taken, filtered through a microporous filter membrane (0.22 μm), and dialyzed to obtain CDs.

[0011] Furthermore, in step 2, the preparation method of the CDs-SA@TAMn nanocomposite is as follows: 10 mg of TAMn nanosheets are dissolved in 20 mL of deionized water, 20 mg of CDs-SA is added, and after continuous stirring for 6 hours, a precipitate is obtained by centrifugation; the precipitate is washed by centrifugation with deionized water to remove impurities in the precipitate, and then the CDs-SA@TAMn nanocomposite is obtained after freeze-drying.

[0012] Furthermore, in step 2, the TAMn nanosheets are prepared by chelation method; first, TA and MnCl2 are added to deionized water and ultrasonically dissolved, followed by stirring at room temperature; then, the pH value of the mixed solution is adjusted to 7.4 by slowly introducing sodium hydroxide, and after stirring the reaction at room temperature, the TAMn precipitate is collected by centrifugation, and finally washed by centrifugation with deionized water.

[0013] Another aspect of the present invention provides the use of the CDs-SA@TAMn nanocomposite described above in the preparation of drugs for treating and preventing breast cancer, especially in chemodynamic / photothermal combined treatment of breast cancer.

[0014] The present invention synthesized orange light CDs by a hydrothermal method, and constructed a nanocomplex (CDs-SA@TAMn) with tumor microenvironment responsiveness based on the CDs. The nanocomplex is simple to prepare, has low toxicity, and has controlled release in the tumor microenvironment. It shows the potential for precise and high-performance anti-tumor therapy in biomedical applications, and can be used for the combined photothermal and chemodynamic treatment of breast cancer. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 Schematic diagram of the preparation and application of CDs-SA@TAMn nanocomposites; Figure 2 TEM images of CDs (a), CDs-SA (b), TAMn (c) and CDs-SA@TAMn (d), particle size distribution of CDs (e) and CDs-SA (f), insets in (a), (b) and (d) are HRTEM images of CDs, CDs-SA and CDs-SA@TAMn, respectively; Figure 3 XRD patterns of CDs, CDs-SA, TAMn and CDs-SA@TAMn; Figure 4 The XPS general spectra of CDs, CDs-SA, TAMn and CDs-SA@TAMn (a), the C1s (b); N1s (c); O1s (d); Mn2p (e) fine spectra of CDs-SA@TAMn; Figure 5UV-visible absorption spectra of CDs, SA, CDs-SA, TAMn and CDs-SA@TAMn; Figure 6 Fluorescence spectra of CDs, SA, CDs-SA, TAMn and CDs-SA@TAMn; Figure 7 FT-IR spectra of CDs, CDs-SA, TA, TAMn and CDs-SA@TAMn; Figure 8 Zeta potential diagrams of CDs, SA, CDs-SA, TAMn and CDs-SA@TAMn; Fig. 9 In the figure, (a) is the temperature change curve of CDs-SA@TAMn with different concentrations under 808 nm (1.8 W) laser irradiation; (b) is the temperature change curve of CDs-SA@TAMn under different power laser irradiation; Fig.10 Temperature variation of H2O, CDs, CDs-SA, TAMn and CDs-SA@TAMn under 808 nm (1.8 W) laser irradiation over time; Fig.11 Infrared thermal imaging images of H2O, CDs, CDs-SA, TAMn and CDs-SA@TAMn changing with time under 808 nm (1.8 W) laser irradiation; Fig.12 Thermal cycle curve of CDs-SA@TAMn under 808 nm laser irradiation; Fig.13 In the figure, (a) is the temperature rise and fall curve of CDs-SA@TAMn irradiated by 808 nm laser (1.8 W); (b) is the linear relationship between time and -ln(θ); Fig.14 The generation of hydroxyl radicals by CDs-SA@TAMn in vitro; Fig.15 The generation of ·OH by CDs-SA@TAMn in PBS solutions with pH values ​​of 5.5, 6.0, and 7.4; Fig.16 The effect of CDs-SA@TAMn on the viability of MCF-7 cells and HUVEC cells; Fig.17 The effects of different treatment groups on the viability of MCF-7 cells (n=6 / group, *, ** and *** represent p<0.05, p<0.01 and p<0.001, respectively); Fig.18Uptake of PBS, CDs, CDs-SA, TAMn and CDs-SA@TAMn by MCF-7 cells; Fig.19 The laser confocal microscope results of CDs after treatment with PBS solution, DNase, RNase and DNase + RNase; Fig. 20 ROS production in PBS group, CDs group, CDs-SA group, TAMn group, and CDs-SA@TAMn group; Fig.21 The killing effects of PBS group, NIR group, CDs-SA group, CDs-SA + NIR group, TAMn + NIR group, CDs-SA@TAMn + NIR group, TAMn + H2O2 group, CDs-SA@TAMn + H2O2 group, TAMn + NIR + H2O2 group, and CDs-SA@TAMn + NIR + H2O2 on MCF-7 cells; Fig. 22 Apoptosis of MCF-7 cells after treatment with PBS, NIR, CDs-SA, CDs-SA + NIR, TAMn + NIR, CDs-SA@TAMn + NIR, TAMn + H2O2, CDs-SA@TAMn + H2O2, TAMn + NIR + H2O2 and CDs-SA@TAMn + NIR + H2O2 (a); apoptosis rate of cells in each group (b) (*, ** and *** represent p<0.05, p<0.01 and p<0.001, respectively); Fig.23 In the figure, (a) is the distribution map of CDs-SA@TAMn in mice, and the fluorescence images were collected at 0, 3, 6, 9, 12, and 24 h after injection; (b) is the fluorescence image of the main organs and tumors of mice 9 h after CDs-SA@TAMn injection; Fig.24 Photothermal imaging of mice injected with saline, CDs, CDs-SA, TAMn, and CDs-SA@TAMn into the tail vein and irradiated with 808 nm (1.8 W) laser for 10 min; Fig.25 Images of mice after two weeks of treatment in different treatment groups (a), tumor images (b), weight changes of mice in different treatment groups during treatment (c), tumor weight changes (d) and relative tumor volume changes (e), (*, ** and *** represent p<0.05, p<0.01 and p<0.001, respectively); Fig.26 Are the blood routine indicators of mice in each group; Fig. 27 Blood biochemical indexes of mice in each group; Fig.28 HE staining images of the main organs (heart, liver, spleen, lung, kidney) and tumor tissues of mice in each group. DETAILED DESCRIPTION

[0016] In the following embodiments, a novel nanocomposite (CDs-SA@TAMn) was constructed and the morphology, elemental composition, optical properties, and surface functional groups of the nanocomposite were analyzed. The fluorescence and photothermal imaging capabilities of the nanocomposite were evaluated by in vitro and cell experiments, confirming the chemodynamic therapy effect and photothermal performance. Balb / c female mice were used as tumor-bearing animal models, and blood routine, biochemical indicators, and HE staining showed that the CDs-SA@TAMn nanocomposite exhibited excellent compatibility in vivo, and the effect of combined tumor therapy was verified based on indicators such as tumor size and relative tumor volume.

[0017] 1. Preparation of CDs-SA@TAMn Nanocomposites 1.1 Preparation of CDs CDs were synthesized by hydrothermal method. 47.5 mg of 1,2,4-triaminobenzene dihydrochloride and 105 mg of spermine were dissolved in deionized water (10 mL). Ultrasonication was performed for 10 min to completely dissolve the solution. The solution was transferred to a polytetrafluoroethylene-lined autoclave. The autoclave was placed in an oven and the temperature was set to 90 °C. The reaction was allowed to react for 12 h and then cooled naturally to room temperature. The cooled solution was centrifuged at 15,000 rpm for 10 min, the supernatant was taken, filtered through a microporous membrane (0.22 μm), and dialyzed for 6 h (MWCO, 500 Da) to obtain a brown solution, which was freeze-dried for later use.

[0018] 1.2 Preparation of CDs-SA Take 20 mg of sialic acid (SA) and disperse it in 10 mL of phosphate buffer solution (PBS, pH 7.4). Add 24 mg of NHS and 24 mg of EDC to the SA solution and stir at room temperature for 15 min to obtain activated SA. Weigh 20 mg of CDs solid and dissolve it in 10 mL of deionized water. After ensuring that CDs are completely dissolved, add the activated SA solution and stir at room temperature for 12 h. The above solution is dialyzed for 6 h (MWCO, 1000 Da) to obtain CDs-SA, which is freeze-dried and set aside.

[0019] 1.3 Preparation of TAMn nanosheets and CDs-SA@TAMn nanocomposites Tannic acid (TA) and divalent metal ions (Mn 2+) TAMn nanosheets were prepared by chelation method

[16] . First, 54 mg TA and 0.881 g MnCl2 were added to 25 mL deionized water and dissolved by ultrasonication, followed by stirring at room temperature for 30 min. Then, the pH value of the mixed solution was adjusted to 7.4 by slowly introducing sodium hydroxide (2 M). After stirring at room temperature for 4 h, the TAMn precipitate was collected by centrifugation (5000 rpm, 5 min), washed three times with deionized water, and freeze-dried for later use.

[0020] 10 mg of TAMn nanosheets were dissolved in 20 mL of deionized water, and 20 mg of CDs-SA was added. After continuous stirring for 6 h, the precipitate was centrifuged (5000 rpm, 5 min). The precipitate was washed by centrifugation with deionized water to remove impurities in the precipitate, and then freeze-dried to obtain the CDs-SA@TAMn nanocomposite.

[0021] 1.4 Characterization of CDs-SA@TAMn nanocomposites The micromorphologies of CDs, CDs-SA, TAMn and CDs-SA@TAMn nanocomposites were characterized by TEM. Figure 2 In (a), the prepared CDs present a uniform spherical structure, and the inset shows that the CDs have a high-resolution lattice with a spacing of 0.21 nm, corresponding to the (100) plane of graphite. Figure 2 (b) TEM image of CDs-SA shows that the spherical structure of CDs-SA is consistent with that of CDs. Figure 2 (b) The inset shows that the lattice spacing of CDs-SA is the same as that of CDs, indicating that the original crystal structure of CDs has not been destroyed. Figure 2 As shown in (c), the prepared TAMn nanosheets have a clear sheet-like structure. Figure 2 (d) is the TEM image of CDs-SA@TAMn nanocomposite, where we can see that CDs-SA nanodots are evenly distributed on TAMn nanosheets. Figure 2 (e)) and CDs-SA ( Figure 2 (f) The particle size distribution diagram shows that the average particle size of CDs is about 1.4 nm, and the average particle size of CDs-SA is 4.6 nm. The particle size of CDs-SA is significantly increased, indicating that SA is successfully connected to CDs.

[0022] Figure 3Figure 2 is the XRD spectrum of CDs, CDs-SA, TAMn and CDs-SA@TAMn. It can be seen from the figure that CDs, CDs-SA and CDs-SA@TAMn nanocomposites have an obvious diffraction peak at 2θ=23.4°, proving that the synthesized CDs and CDs-SA have an amorphous carbon structure. The position of the characteristic diffraction peak of TAMn nanosheets remains unchanged after CDs-SA is loaded, indicating that CDs-SA does not affect the crystalline structure of TAMn nanosheets.

[0023] The elemental compositions of CDs, CDs-SA, TAMn and CDs-SA@TAMn were characterized by XPS. Figure 4 As shown in (a), CDs and CDs-SA only contain C, N, and O elements, TAMn contains C, O, and Mn elements, and CDs-SA@TAMn is composed of four elements: C, N, O, and Mn. The relative contents of each element are shown in Table 1. Figure 4 (b) shows the C1s fine-scale spectrum of the CDs-SA@TAMn nanocomposite, where the peaks at 284.6 eV, 285.4 eV, 287.5 eV, and 288.6 eV correspond to the binding energies of CC, CN, CO, and C=O bonds, respectively. . N1s fine spectrum such as Figure 4 (c) shows that the peaks at 398.7eV, 399.6eV and 400.9eV are caused by pyridine N, pyrrole N and graphite N, respectively. . O1s fine spectrum ( Figure 4 In (d), the peaks at 530.4 eV, 531.8 eV, and 533.3 eV are derived from the binding energy of C=O, CO, and COC.

[22] .Depend on Figure 4 (e) In the Mn2p fine spectrum, the peaks at 640.9 eV and 653.2 eV are attributed to Mn2p 2 / 3 and Mn2p 1 / 3 The binding energy.

[0024] Table 1 Element contents of CDs, CDs-SA, TAMn and CDs-SA@TAMn

[0025] The UV absorption spectra of CDs, CDs-SA, TAMn and CDs-SA@TAMn were investigated by UV-visible spectrophotometer. Figure 5As shown in the figure, CDs has an absorption peak at 445 nm, which is caused by the n-π* transition of the conjugated C=O / C=N bond. The absorption peak of CDs-SA at 445 nm is weakened, which is attributed to the amide reaction between CDs and SA. TAMn nanosheets have a wide range of ultraviolet absorption in the range of 300-900 nm. After the introduction of CDs-SA, the ultraviolet absorption of CDs-SA@TAMn nanocomposites in the range of 300-900 nm increases and the characteristic absorption peak of CDs appears, indicating that CDs-SA is successfully loaded on TAMn nanosheets. The fluorescence properties of CDs, CDs-SA, TAMn and CDs-SA@TAMn were studied by fluorescence spectrophotometer. The results are shown in Figure 6 As shown in the figure, the maximum excitation wavelength of CDs is 445 nm and the maximum emission wavelength is 592 nm. After modification with SA, the fluorescence intensity of CDs-SA decreases. TAMn nanosheets themselves have no fluorescence, and CDs-SA@TAMn nanocomposites show weak fluorescence at 592 nm, indicating the successful adsorption of CDs-SA.

[0026] The surface functional group characteristics of CDs, CDs-SA, TAMn and CDs-SA@TAMn were characterized. Figure 7 As shown, CDs at 3432 cm -1 、3219 cm -1 、2945 cm -1 、1650 cm -1 、1570 cm -1 、1497 cm -1 and 1328 cm -1 There are characteristic absorption peaks at 3432 cm -1 and 3219 cm -1 The characteristic peaks are related to the stretching vibrations of OH and NH; 2945cm -1 、1650 cm -1 and 1570 cm -1 The characteristic peaks at 1497cm are caused by the stretching vibrations of the CH bond, C=O bond, and NH bond; -1 and 1328 cm -1 The obvious characteristic peaks at 1650 cm-1 are caused by the C=C bond and CN stretching vibration, which further proves that the CDs surface contains abundant amino groups. -1 The characteristic absorption peak intensity at 3219 cm is increased, which is due to the amide bond generated by the interaction between the carboxyl group of SA and the amine group of CDs. CDs-SA@TAMn nanocomposite 3219 cm -1 and 861 cm -1The characteristic absorption peaks appearing at are attributed to the stretching vibration of the NH bond on the CDs surface and the stretching vibration of the CH bond of the benzene ring in TAMn. From the potential diagrams of CDs, CDs-SA, TAMn and CDs-SA@TAMn ( Figure 8 ) It can be seen that due to the abundant amino groups on the surface of CDs, the potential of CDs is 20.4 mV. After SA and CDs undergo amide reaction, the potential of CDs-SA decreases to 17.3 mV. The potential of TAMn is -13.7 mV, indicating that CDs-SA can be adsorbed on the surface of TAMn nanosheets through electrostatic adsorption.

[0027] 2. In vitro photothermal performance measurement of CDs-SA@TAMn nanocomposites In order to explore the in vitro photothermal effect of CDs-SA@TAMn solution, an 808 nm laser was selected as the light source, and the irradiation experiment of CDs-SA@TAMn solution with different concentrations was carried out for 10 min at a laser power of 1.8 W. Fig. 9 (a) shows that as the concentration of CDs-SA@TAMn solution increases, its temperature also shows an obvious upward trend. When the solution concentration reaches 200 μg / mL, the temperature of the solution can rise to 58.7℃ after 10 min of laser irradiation. Fig. 9 (b) is the temperature change diagram of CDs-SA@TAMn solution under different light power irradiation. It can be seen from the figure that the temperature of CDs-SA@TAMn solution increases with the increase of laser power.

[0028] like Fig.10 As shown in the figure, under the irradiation of 808 nm laser (power of 1.8 W), after 10 min of irradiation, the temperature of the PBS group solution did not rise significantly, while the solution temperatures of the CDs group, CDs-SA group, TAMn group and CDs-SA@TAMn group increased to 44.5℃, 41.9℃, 52.0℃ and 58.7℃, respectively. The CDs-SA@TAMn group showed the highest temperature rise under the same conditions, indicating that it has a good photothermal effect.

[0029] Fig.11 The photothermal images of H2O, CDs, CDs-SA, TAMn and CDs-SA@TAMn show that the temperature of CDs-SA@TAMn solution increased significantly under 808 nm (1.8 W) laser irradiation, indicating that CDs-SA@TAMn nanocomposite has excellent photothermal effect and can be further used for in vivo photothermal imaging.

[0030] Thermal cycling experiments were used to evaluate the photothermal stability of CDs-SA@TAMn nanocomposites. The solution was irradiated with an 808 nm laser with a power of 1.8 W for 10 min. After the irradiation, the laser was turned off and cooled for 10 min. The above operation was repeated 5 times. The results are shown in Figure 2. Fig.12 The results show that after 5 photothermal cycle tests, the maximum temperature of the CDs-SA@TAMn solution remained stable, demonstrating its excellent photostability.

[0031] By analyzing the heating and cooling curves ( Fig.13 (a)) and the linear relationship between time and -ln(θ) ( Fig.13 (b) ), and calculate τ s is 319. The calculated photothermal conversion efficiency of CDs-SA@TAMn nanocomposite is 29.6%, which can be used for photothermal therapy.

[0032] 3. In vitro chemokinetic effect of CDs-SA@TAMn nanocomposites Terephthalic acid was used to test the generation of hydroxyl radicals in vitro. Fig.14 As shown in the figure, the terephthalic acid + H2O2 + CDs-SA@TAMn group produced an obvious fluorescence signal at 425 nm and the fluorescence intensity was higher than that of other groups, proving that Mn 2 + It can react with H2O2 to produce ·OH in a Fenton-like reaction.

[0033] Terephthalic acid was used as a probe to detect the generation of ·OH in CDs-SA@TAMn in phosphate buffer solutions at pH 5.5, 6.0, and 7.4. Fig.15 The results of the generation of ·OH by CDs-SA@TAMn in different pH conditions are shown in the figure. As can be seen from the figure, in a solution with a pH of 5.5, the fluorescence intensity at 425 nm reached the highest value. This result indicates that weakly acidic conditions promote the process of CDs-SA@TAMn catalyzing H2O2 to generate ·OH, and it has potential application value in the field of chemodynamic therapy.

[0034] 4. Cell experiments of CDs-SA@TAMn nanocomposites 4.1 Cytotoxicity assay The MTT assay was used to evaluate the dark toxicity of CDs-SA@TAMn on MCF-7 cells and HUVEC cells. Fig.16It can be seen that after incubation with different concentrations of CDs-SA@TAMn (0, 25, 50, 75, 100, 125, 150, 175, 200 μg / mL), the survival rates of MCF-7 cells and HUVEC cells were maintained at a high level of more than 85%. The results show that the CDs-SA@TAMn nanocomposite did not cause significant toxic effects on cells, showing its good biocompatibility. The therapeutic effect was evaluated by detecting the survival rate of MCF-7 cells after treatment with different materials. The results are shown in Figure 2. Fig.17 As shown in the figure, the cell survival rates of the CDs-SA+NIR group, TAMn+H2O2+NIR group, CDs-SA@TAMn+H2O2 group and CDs-SA@TAMn+ NIR group (200 μg / mL) after treatment were 76.8%, 29.8%, 63.8% and 58.0%, respectively, indicating that single chemodynamic therapy and single photothermal therapy have certain killing effects on MCF-7 cells. After treatment with the CDs-SA@TAMn+H2O2+NIR group, the cell survival rate decreased to 12.7%, indicating that the CDs-SA@TAMn+H2O2+NIR group had the best anti-tumor effect after combined chemodynamic and photothermal therapy.

[0035] 4.2 Cellular uptake experiments The uptake of CDs, CDs-SA, TAMn and CDs-SA@TAMn by MCF-7 cells was studied. DAPI stain was used to locate the cell nucleus. Fig.18 As shown in the figure, after incubation with CDs, the nucleus of MCF-7 cells showed orange fluorescence at an emission wavelength of 590 nm, and the fluorescence intensity of the nucleolus was higher than that of the nucleus, indicating that CDs can selectively enter the nucleolus of the cell nucleus. The fluorescence intensity at the nucleolus of the CDs-SA group was slightly stronger than that of CDs, indicating that SA has a certain targeting ability for MCF-7 cells. Although the CDs-SA@TAMn group lost its nucleolus targeting ability, it still had fluorescence distributed in the cytoplasm and nucleus, indicating that it has good cell uptake ability.

[0036] 4.3 Nuclease digestion experiment of CDs To explore the specific targeting ability of CDs to the nucleolus, MCF-7 cells were subjected to enzymatic hydrolysis experiments using RNase and DNase. DAPI mainly stains the cell nucleus. After the cells are stained with DAPI, the cell nucleus will show blue fluorescence. Fig.19It can be seen that when cells are treated with RNase, the RNA in the cells will be degraded, and the fluorescence intensity originally concentrated in the nucleolus will decrease, but it will still target the nucleolus. When cells are treated with DNase, the DNA in the cells will be catalytically degraded, and the fluorescence intensity of DAPI will be significantly reduced, but the nucleolus of the cells will still show bright fluorescence. In cells digested with DNase and RNase at the same time, the fluorescence is evenly distributed throughout the cell, and the labeling characteristics of the nucleolus are obviously lost. This shows that CDs can bind to DNA and RNA when entering the nucleolus, but prefer to interact with RNA.

[0037] 4.4 Intracellular reactive oxygen species detection DCFH-DA was used to detect the level of ·OH production in each group of cells. Fig. 20 As shown in the figure, DCFH can be oxidized to green fluorescent DCF in the presence of reactive oxygen species. MCF-7 cells incubated with PBS, CDs, and CDs-SA groups did not show green fluorescence, indicating that no reactive oxygen species were produced in the cells. Green fluorescence was observed in both the TAMn group and the CDs-SA@TAMn group, and the fluorescence signal of the CDs-SA@TAMn group was stronger than that of the TAMn group, indicating that Mn 2+ It can undergo a Fenton-like reaction with H2O2 to generate ·OH, which can be further used in the chemodynamic therapy of tumors.

[0038] 4.5 Live and dead cell staining experiment The Calcein-AM / PI live / dead cell double staining kit was used to evaluate the therapeutic effects of different treatment groups on MCF-7 cells. Calcein-AM / PI was co-incubated with MCF-7 cells. Under an excitation wavelength of 490 nm, live cells would show green fluorescence, and under an excitation wavelength of 535 nm, PI would enter the nuclei of dead cells and show red fluorescence. Fig.21 It can be seen that the cells in the PBS group, NIR group and CDs-SA group only showed green fluorescence, indicating that PBS and CDs-SA incubation or laser irradiation had no killing effect on the cells. The CDs-SA + NIR group, TAMn + NIR group, CDs-SA@TAMn + NIR group, TAMn + H2O2 group, CDs-SA@TAMn + H2O2 group and TAMn + NIR + H2O2 group all showed red fluorescence signals in different proportions, indicating that they can kill tumor cells to different degrees. The CDs-SA@TAMn + NIR + H2O2 group showed red fluorescence signals and almost all cells died, indicating that the combined treatment had the best effect.

[0039] 4.6 Cell apoptosis assay Annexin V-FITC / PI double staining was used to evaluate the effects of ①PBS group, ②NIR group, ③CDs-SA group, ④CDs-SA + NIR group, ⑤TAMn + NIR group, ⑥CDs-SA@TAMn + NIR group, ⑦TAMn + H2O2 group, ⑧CDs-SA@TAMn +H2O2 group, ⑨TAMn + NIR + H2O2 group and ⑩CDs-SA@TAMn + NIR + H2O2 group on MCF-7 cell apoptosis. The experimental results are shown in Fig. 22 (a) and Fig. 22 (b). The cell apoptosis rates of the PBS group, NIR group and CDs-SA group were all below 10%, indicating that simple laser irradiation and CDs-SA incubation did not trigger cell apoptosis. A certain proportion of cell apoptosis occurred in the CDs-SA + NIR group, TAMn + NIR group, CDs-SA@TAMn + NIR group, TAMn + H2O2 group, CDs-SA@TAMn + H2O2 group, TAMn + NIR + H2O2 group and CDs-SA@TAMn + NIR + H2O2 group, and the cell apoptosis rate in the combined treatment group (CDs-SA@TAMn + NIR + H2O2) was the highest. The experimental results showed that the combined strategy of chemodynamic therapy and photothermal therapy can effectively induce cancer cell apoptosis.

[0040] 5. Animal model experiments of CDs-SA@TAMn nanocomposites 5.1 Establishment of mouse tumor model Six-week-old Balb / c female mice were selected for the establishment of model mice. First, the right armpit of the mouse was depilated, and then the serum-free 1640 culture medium containing 4T1 cells was inoculated into the right armpit of the mouse. After the inoculation, the health status of the mouse and the growth of the tumor were closely observed every day. When the tumor volume grew to 100mm 3 The mice were divided into groups for subsequent experiments.

[0041] 5.2 Fluorescence imaging of mice 200 μL of normal saline containing CDs-SA@TAMn (2 mg / mL) was injected into two groups of tumor-bearing mice through the tail vein. One group used a fluorescence imaging system to record the images at different time points (0, 3, 6, 9, 12, and 24 h), and the other group obtained the heart, liver, spleen, lung, kidney, and tumor tissues of the mice when the fluorescence accumulation in the body was strongest to analyze the distribution of CDs-SA@TAMn in the organs in the body.

[0042] Depend on Fig.23(a) It can be seen that after CDs-SA@TAMn was injected into the tail vein, it first appeared in the liver, and then the fluorescence intensity of the tumor site gradually increased. At 9 h after injection, the fluorescence signal of CDs-SA@TAMn reached a peak, proving that CDs-SA@TAMn can be effectively enriched in the tumor site. As time goes by, the fluorescence intensity of the tumor site gradually decreases, and the fluorescence intensity of the liver site gradually increases. It can be seen that CDs-SA@TAMn is gradually eliminated from the body through liver metabolism in the body circulation, indicating that CDs-SA@TAMn can be quickly metabolized by the mouse circulatory system, reducing the risk of biological toxicity. Fig.23 (b) is the fluorescence image of mouse organs and tumors 9 hours after injection of CDs-SA@TAMn. It can be seen that the fluorescence intensity at the mouse tumor site is the highest, indicating that CDs-SA@TAMn has a certain targeting effect on tumor cells.

[0043] 5.3 Photothermal imaging of mice Five tumor-bearing mice were selected and physiological saline, CDs, CDs-SA, TAMn and CDs-SA@TAMn were injected into the mice through the tail vein. After 9 hours, the tumor site was irradiated with 808 nm laser (1.8 W). At the same time, a near-infrared imager was used to take pictures and record the temperature changes at different times to observe the aggregation of different materials at the tumor site.

[0044] The photothermal imaging of mice was recorded using a near-infrared imager. Fig.24 As shown in the figure, after 10 minutes of 808 nm laser irradiation, there was no obvious temperature increase in the saline group, but the temperature in the CDs-SA@TAMn group increased significantly and the temperature at the tumor site was the highest, indicating that the material can accumulate at the tumor site and has good photothermal imaging capabilities. 5.4 In vivo tumor treatment effects To study the effects of different treatments on tumor growth, tumor-bearing mice were randomly assigned to eight different groups, each containing five mice. After 14 days of treatment, photos of mice in each group and photos of dissected tumors were taken. Fig.25 (a) and Fig.25 (b) As shown. The tumor sizes of the NIR group and the CDs-SA group were similar to those of the saline group, indicating that they could not inhibit tumor growth. The tumors of the CDs-SA+NIR group were slightly smaller than those of the saline group, and the tumors of the TAMn group, TAMn +NIR group, and CDs-SA@TAMn group were significantly smaller than those of the PBS group, indicating that they played a tumor inhibitory role to a certain extent. The tumors in the CDs-SA@TAMn+NIR group almost completely disappeared, proving that it had the highest tumor inhibition rate and the combined treatment had a good effect. The average body weight of mice treated for 14 days is shown in Figure 2. Fig.25 As shown in (c), there was no significant change in the body weight of mice in each group. Fig.25 (d) is the average weight of tumors in each group after 14 days of treatment. Fig.25 (e) is the relative tumor volume of mice, showing a highly efficient tumor inhibition rate in the combined treatment group, with significant therapeutic effects.

[0045] 5.5 Biosafety Assessment The biocompatibility of CDs-SA@TAMn nanocomposites was evaluated by blood routine tests, liver and kidney indexes detection and HE staining. Fig.26 and Fig. 27 The results of blood routine tests (WBC, RBC, PLT, MCH, MCV, MCHC, HCT, HGB) and blood biochemical indexes (ALT, AST, ALB, TP, BUN, CRE) of each group of mice were shown. All the indexes of each group were within the normal range, indicating that the CDs-SA@TAMn nanocomposite had no obvious negative impact on the mouse body and had excellent biocompatibility. Fig.28 As shown, the HE staining results of the heart, liver, spleen, lung, kidney and tumor tissues of the mice showed that there were almost no physiological and morphological abnormalities or histopathological damage in the main organs of the mice. The tumor tissues of the CDs-SA + NIR group, TAMn group, TAMn + NIR group and CDs-SA@TAMn group showed partial ablation, and the tumor tissue of the CDs-SA@TAMn group had obvious large-area ablation, which also shows that the combined chemodynamic and photothermal therapy is the best.

Claims

1. A CDs-SA@TAMn nanocomposite, characterized in that: include: CDs-SA is a method of modifying the surface of CDs with sialic acid (SA) by reacting the carboxyl group on the surface of SA with the amino group on the surface of CDs to form an amide. TAMn, as a carrier, loads CDs-SA.

2. The method for preparing the CDs-SA@TAMn nanocomposite according to claim 1, characterized in that: The following steps are involved: Step 1, preparing CDs-SA; Sialic acid (SA) is dispersed in a phosphate buffer solution to obtain a SA solution, NHS and EDC are added to the SA solution and stirred at room temperature to obtain an activated SA solution; CDs are dissolved and added to the activated SA solution, stirred sufficiently at room temperature, and dialyzed to obtain CDs-SA; Step 2, preparation of CDs-SA@TAMn nanocomposites; The TAMn nanosheets were dissolved in deionized water, and then the CDs-SA obtained in step 1 was added, and the CDs-SA@TAMn nanocomposite was obtained after stirring, centrifugation, washing, and freeze-drying.

3. The preparation method according to claim 2, characterized in that: In step 1, 20 mg of sialic acid (SA) was dispersed in 10 mL of pH 7.4 phosphate buffer solution, 24 mg of NHS and 24 mg of EDC were added to the SA solution and stirred at room temperature for 15 min to obtain activated SA.

4. The preparation method according to claim 3, characterized in that: In step 1, 20 mg of CDs solid was weighed and dissolved in 10 mL of deionized water. After the CDs were completely dissolved, the activated SA solution was added and stirred at room temperature for 12 h. The obtained solution was then dialyzed to obtain CDs-SA.

5. The preparation method according to claim 2, 3 or 4, characterized in that: In step 1, the CDs are synthesized by a hydrothermal method, 1,2,4-triaminobenzene dihydrochloride and spermine are dissolved in deionized water, and the obtained solution is reacted at 90°C for 12 hours and naturally cooled to room temperature; the cooled solution is centrifuged at 15,000 rpm for 10 minutes, the supernatant is taken, filtered through a microporous filter membrane (0.22 μm), and dialyzed to obtain CDs.

6. The preparation method according to claim 5, characterized in that: In step 2, the preparation method of the CDs-SA@TAMn nanocomposite is as follows: 10 mg of TAMn nanosheets are dissolved in 20 mL of deionized water, 20 mg of CDs-SA is added, and after continuous stirring for 6 hours, a precipitate is obtained by centrifugation; the precipitate is washed by centrifugation with deionized water to remove impurities in the precipitate, and then the CDs-SA@TAMn nanocomposite is obtained after freeze-drying.

7. The preparation method according to claim 6, characterized in that: In step 2, TAMn nanosheets are prepared by chelation method; first, TA and MnCl2 are added to deionized water, ultrasonically dissolved and stirred at room temperature; then, the pH value of the mixed solution is adjusted to 7.4 by slowly introducing sodium hydroxide, and after stirring the reaction at room temperature, the TAMn precipitate is collected by centrifugation and finally washed by centrifugation with deionized water.

8. Use of the CDs-SA@TAMn nanocomposite according to claim 1 in preparing drugs for treating and preventing breast cancer.